Use of a Business Approach to Improve Disease Surveillance Data Management Systems and Information Technology Process comprehensive review - Ranjes Abbas Alshala et al. (International Journal of Scientific Research and Innovative Studies, 2024)
The increasing complexity of global disease outbreaks necessitates robust and efficient disease surveillance data management systems (DSDMS). Traditionally, disease surveillance has been managed within public health frameworks, focusing on public health-specific methodologies. However, integrating business approaches such as Business Process Management (BPM), strategic planning, risk management, and IT governance into these models and modern technologies, emphasizing the need for data governance, cross-sector collaboration, and continuous improvement. Received Date: September 14, 2024 Accepted Date: October 12, 2024 Published Date: November 13, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/315 https://doi.org/10.5281/zenodo.14793550